2017
DOI: 10.1016/j.neuroimage.2016.12.056
|View full text |Cite
|
Sign up to set email alerts
|

Construction and modeling of a reconfigurable MRI coil for lowering SAR in patients with deep brain stimulation implants

Abstract: Post-operative MRI of patients with deep brain simulation (DBS) implants is useful to assess complications and diagnose comorbidities, however more than one third of medical centers do not perform MRIs on this patient population due to stringent safety restrictions and liability risks. A new system of reconfigurable magnetic resonance imaging head coil composed of a rotatable linearly-polarized birdcage transmitter and a close-fitting 32-channel receive array is presented for low-SAR imaging of patients with D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 50 publications
2
64
0
Order By: Relevance
“…All temperature measurements were performed on a Siemens 3T whole‐body Prisma scanner (Siemens, Erlangen, Germany) with a head‐only, single‐channel, 16‐rung RF Tx/Rx coil. All studies used an ASTM (American Society for Testing and Materials) whole‐body phantom filled with polyacrylic acid gelled saline (ASTM F2182‐02a, West Conshohocken, PA) having thermal and electrical properties similar to that of human tissue . The gel was prepared by rigorously mixing 24 g of NaCl and 175.4 g of polyacrylic acid (Sigma‐Aldrich Corp, St. Louis, MO) into 30 L of deionized water.…”
Section: Methodsmentioning
confidence: 99%
“…All temperature measurements were performed on a Siemens 3T whole‐body Prisma scanner (Siemens, Erlangen, Germany) with a head‐only, single‐channel, 16‐rung RF Tx/Rx coil. All studies used an ASTM (American Society for Testing and Materials) whole‐body phantom filled with polyacrylic acid gelled saline (ASTM F2182‐02a, West Conshohocken, PA) having thermal and electrical properties similar to that of human tissue . The gel was prepared by rigorously mixing 24 g of NaCl and 175.4 g of polyacrylic acid (Sigma‐Aldrich Corp, St. Louis, MO) into 30 L of deionized water.…”
Section: Methodsmentioning
confidence: 99%
“…1 MCR-WPT technology can be extended to military, aerospace, coal mining, medical implantation, household appliances, wireless sensor networks, electric vehicles, safety monitoring of buildings and other fields, owing to the advantages of higher transmission efficiency, bigger transmission power, smaller electromagnetic radiation and longer transmission distance. [2][3][4][5][6][7][8] Therefore, it is considered to be one of the most potential techniques for mid-range WPT applications at present.…”
Section: Introductionmentioning
confidence: 99%
“…He found that the temperature alteration near the DBS leads was within 1°, which is acceptable . Dr. Golestanirad and his team tested the influences of different wire arrangements and different MRI scanners on the heating of DBS leads and found that some specific setups are conducive for decreasing temperature alterations. Considering these findings, a higher magnitude may not necessarily be accompanied by increased risks of heating injury.…”
Section: Discussionmentioning
confidence: 99%